Preface - Dimyati, Kaharuddin (New Explorations in Electrical Engineering, 2025)
It is with great enthusiasm that we present the inaugural issue of New Explorations in Electrical Engineering (NECE), the official journal of the Department of Electrical Engineering, Faculty of Engineering, Universiti Malaya. This journal marks a significant milestone in our commitment to fostering a culture of research and academic writing among faculty members and students while providing a collaborative platform for sharing knowledge and technical advancements within the broader electrical engineering community.